Management of vertebral radiotherapy dose in paediatric patients with cancer: consensus recommendations from the SIOPE radiotherapy working group - Hoeben, Bianca A; Carrie, Christian; Timmermann, Beate; Mandeville, Henry C; Gandola, Lorenza; Dieckmann, Karin; Ramos Albiac, Monica; Magelssen, Henriette; Lassen-Ramshad, Yasmin; Ondrová, Barbora; Ajithkumar, Thankamma; Alapetite, Claire; et al. (The Lancet. Oncology, 2019)
Inhomogeneities in radiotherapy dose distributions covering the vertebrae in children can produce long-term spinal problems, including kyphosis, lordosis, scoliosis, and hypoplasia. In the published literature, many often interrelated variables have been reported to affect the extent of potential radiotherapy damage to the spine. Articles published in the 2D and 3D radiotherapy era instructed radiation oncologists to avoid dose inhomogeneity over growing vertebrae. However, in the present era of highly conformal radiotherapy, steep dose gradients over at-risk structures can be generated and thus less harm is caused to patients. In this report, paediatric radiation oncologists from leading centres in 11 European countries have produced recommendations on how to approach dose coverage for target volumes that are adjacent to vertebrae to minimise the risk of long-term spinal problems. Based on available information, it is advised that homogeneous vertebral radiotherapy doses should be delivered in children who have not yet finished the pubertal growth spurt. If dose fall-off within vertebrae cannot be avoided, acceptable dose gradients for different age groups are detailed here. Vertebral delineation should include all primary ossification centres and growth plates, and therefore include at least the vertebral body and arch. For partial spinal radiotherapy, the number of irradiated vertebrae should be restricted as much as achievable, particularly at the thoracic level in young children (<6 years old). There is a need for multicentre research on vertebral radiotherapy dose distributions for children, but until more valid data become available, these recommendations can provide a basis for daily practice for radiation oncologists who have patients that require vertebral radiotherapy.
Keywords: předškolní dítě; nádory; Child; Radiotherapy Dosage; Humans; lidé; Radiotherapy, Conformal; Neoplasms; celková dávka radioterapie; Female; Male; pediatrie; konformní radioterapie; Radiation Oncology; Pediatrics; mužské pohlaví; radiační onkologie; ženské pohlaví; Child, Preschool; dítě